Globalisation and the Prevalence of Superstitious Beliefs - Sonia George and Krishna Prasad Sreedhar (Journal of the Indian Academy of Applied Psychology July 2006, Vol. 32, No. 3, 241-247., 2006)
A sample of 180 Post-Graduate students was selected in order to find out the existence of superstitious beliefs and whether faculty difference and sex difference have any influence upon the irrational superstitious beliefs. Religious and urbanrural differences were also studied. It was found that 48 percent of the items were responded positively by the students, indicating the prevalence of superstitious beliefs in the modern educated youth. Subject faculty difference did not have any influence on the superstitious beliefs indicating that none of the three streams of education contribute to a decrement in the intensity of such beliefs. Sex difference had much effect on the irrational belief variables, with females possessing more irrational beliefs than males. This urges us to think about the improvements that are to be made in their case. Among the three religious groups, Christians were found to have least belief in superstitions, Muslims having the most and Hindus coming in between them. Place of residence also had significant effect with students coming from urban area believing more in superstitions than those coming from rural area. All these show that superstitious beliefs still persist in this age of globalization and that effective steps are to be taken to find out the causes for their prevalence and to eliminate them.